2015
DOI: 10.2147/ppa.s84297
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of training at the anaerobic threshold in addition to pharmacotherapy on weight loss, body composition, and exercise performance in women with obesity

Abstract: ObjectiveThe aim of this study was to determine and compare the effects of weight loss achieved through orlistat therapy alone or a combination of orlistat and an aerobic exercise training program on aerobic fitness and body composition in obese females.MethodsTwenty-eight obese patients were randomly assigned to receive 12-week treatment with hypocaloric diet–orlistat or diet–orlistat–exercise. Each participant performed an incremental ramp exercise test every 4 weeks to measure aerobic fitness. Fourteen part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 27 publications
(30 reference statements)
1
16
0
1
Order By: Relevance
“…It has been revealed that BIA is a useful, easily applicable, and inexpensive tool for the evaluation of body composition of obese [10], cardiometabolic disorders [1][2][3][4], cancer [8], and hemodialysis patients [18]. Obtaining confidential information with regarding specific proportion of each section of body composition (TBW, FFM, %FM and FM) in health and also some disorder is a continue interest of clinical and scientist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been revealed that BIA is a useful, easily applicable, and inexpensive tool for the evaluation of body composition of obese [10], cardiometabolic disorders [1][2][3][4], cancer [8], and hemodialysis patients [18]. Obtaining confidential information with regarding specific proportion of each section of body composition (TBW, FFM, %FM and FM) in health and also some disorder is a continue interest of clinical and scientist.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately in the last five years, it has been suggested that body composition could be assessed by measuring resistance to electrical activity from different parts of the body [7]. This method has been termed as bioelectrical impedance analysis (BIA) and widely used for evaluation of body compartments in many clinical and non-clinical situations [8][9][10]. BIA is considered to be easily, noninvasively, quickly applied non-invasive method and provide reliable outcome in research and clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Regular physical activity and exercise studies have a major importance in the treatment, rehabilitation and prevention of various diseases including cardiac, metabolic, and respiratory systems (1,3,4). However, despite the beneficial effects on health, acute exercise may also cause an increased oxidative stress in the body (5).…”
Section: Introductionmentioning
confidence: 99%
“…Exercise is an effective stimulatory factor on energy metabolic systems (4). In addition acute exercise may cause a significant increase in levels of oxidative stress in body (5,6).…”
Section: Introductionmentioning
confidence: 99%